The effects of gastrocnemius–soleus muscle forces on ankle biomechanics during triple arthrodesis. Issue 2 (25th January 2017) - Hejazi, S.; Rouhi, G.; Rasmussen, J.
Abstract: This paper presents a finite element model of the ankle, taking into account the effects of muscle forces, determined by a musculoskeletal analysis, to investigate the contact stress distribution in the tibio-talar joint in patients with triple arthrodesis and in normal subjects. Forces of major ankle muscles were simulated and corresponded well with the trend of their EMG signals. These forces were applied to the finite element model to obtain stress distributions for patients with triple arthrodesis and normal subjects in three stages of the gait cycle, i.e. heel strike, midstance, and heel rise. The results demonstrated that the stress distribution patterns of the tibio-talar joint in patients with triple arthrodesis differ from those of normal subjects in investigated gait cycle stages. The mean and standard deviations for maximum stresses in the tibo-talar joint in the stance phase for patients and normal subjects were 9.398e7 ± 1.75e7 and 7.372e7 ± 4.43e6 Pa, respectively. The maximum von Mises stresses of the tibio-talar joint for all subjects in the stance phase found to be on the lateral side of the inferior surface of the joint. The results also indicate that, in patients with triple arthrodesis, increasing gastrocnemius–soleus muscle force reduces the stress on the medial malleolus compared with normal subjects. Most of stresses in this area are between 45 and 109 kPa, and will decrease to almost 32 kPa in patients after increasing of 40% in gastrocnemius–soleus muscle force.